Deep juvenile xanthogranuloma. - Bonifazi, E.; Garofalo, L; Milano, A. (European Journal of Pediatric Dermatology, 2010)
A 2-month-old boy was first observed due to a nodule on the right leg arisen at the age of 1 month and rapidly grown. Physical examination showed over the right heel a 3 cm, round, skin colored nodule, which tended the overlying epidermis where some telangiectasias were noted (Fig. 1). The nodule on palpation had a hard-elastic consistency and was movable on the deep layers. The physical examination of other organs and systems was negative and all laboratory tests were within normal limits. Magnetic resonance imaging (Fig. 2) showed a clearly demarcated nodule that extended in extra-fascial site, compressed and displaced the vascular bundle and the Achilles tendon. The nodule was removed under general anesthesia and histologic examination surprisingly showed a xanthomized histiocytic infiltrate (Fig. 3) with Touton cells (Fig. 3, inset), leading to the final diagnosis of juvenile xanthogranuloma.